(untitled) (European Journal of Health Research, 2018)
Gender identity satisfaction in boys and girls it is seldom subject of research. We suggest that the difference in satisfaction lies in the assigned roles and gender stereotypes imposed by culture for each gender, being the male role socially most valued. The purpose of this study is to assess the gender identity satisfaction in boys and girls according to sex and age. We worked with a sample of 435 participants from ages of 3 to 7, consisted of 223 girls (50.1%) and 222 boys (49.9%) who were randomly recruited from schools of Navarra for this cross-sectional and descriptive study. We used the semi-structured interview: Boys and girls ¿equal or different? The results obtained showed that satisfaction is high in all ages, but significantly higher in boys, increasing the difference between both sexes with age. Among all ages, the reasons for satisfaction will be based on the assumption of roles and stereotypes assigned to each gender.